The abdominal wall incisional hernia repair in cirrhotic patients - LICARI, L. (G Chir, 2018)
BACKGROUND: The incidence of abdominal wall hernia in cirrhotic patients with ascites is between 20 and 40%. Controversies regarding the treatment modality and surgical timing of abdominal wall incisional hernia repair in cirrhotic patients remain. The study proposed wants to analyze the abdominal incisional hernia repair in cirrhotic patients with ascites performed in a single center to determine post-operative morbidity, mortality and complication rate. PATIENTS AND METHODS: Cirrhotic patients with abdominal incisional hernia that underwent surgical operation for abdominal wall hernia repair at the “Policlinico Paolo Giaccone” at Palermo University Hospital between January 2015 and December 2016 were identified and the data collected were retrospectively reviewed; patients’ medical and surgical records were collected from charts and the surgical and ICU registries. The degree of hepatic dysfunction was classified using Child-Pugh classification. Post-operative mortality was considered up to 30-days after surgery. A follow-up period of 6 months at least was performed to evaluate hernia recurrence and complications. RESULTS: Mortality rate is of 18.5% (p 0.002). Recurrence rate (p 0.004) and seroma formation rate (p 0.001) are most frequent in urgency group. The elevated ASA score and the prediction of a complicated post-operative course is higher in urgency group (p 0.004) as higher is the in-hospital stay (p 0.001) and the ICU stay (p 0.001). CONCLUSIONS: Elective surgery for abdominal wall hernia repair in cirrhotic patients seems to be successful and associated with lower mortality/morbidity rate and recurrence rate than urgency.